The development and initial validation of the PROMIS®+HF‐27 and PROMIS+HF‐10 profiles. (15th July 2022) - Ahmad, Faraz S.; Jackson, Kathryn L.; Yount, Susan E.; Rothrock, Nan E.; Kallen, Michael A.; Lacson, Leilani; Bilimoria, Karl Y.; Kho, Abel N.; Mutharasan, Raja Kannan; McCullough, Peter A.; Bruckel, Jeffrey; Fedson, Savitri; et al.
Abstract: Aims: Heart failure (HF) is a common and morbid condition impacting multiple health domains. We previously reported the development of the PROMIS®‐Plus‐HF (PROMIS+HF) profile measure, including universal and HF‐specific items. To facilitate use, we developed shorter, PROMIS+HF profiles intended for research and clinical use. Methods and results: Candidate items were selected based on psychometric properties and symptom range coverage. HF clinicians ( n = 43) rated item importance and clinical actionability. Based on these results, we developed the PROMIS+HF‐27 and PROMIS+HF‐10 profiles with summary scores (0–100) for overall, physical, mental, and social health. In a cross‐sectional sample ( n = 600), we measured internal consistency reliability (Cronbach's alpha and Spearman–Brown), test–retest reliability (intraclass coefficient; n = 100), known‐groups validity via New York Heart Association (NYHA) class, and convergent validity with Kansas City Cardiomyopathy Questionnaire (KCCQ) scores. In a longitudinal sample ( n = 75), we evaluated responsiveness of baseline/follow‐up scores by calculating mean differences and Cohen's d and comparing with paired t ‐tests. Internal consistency was good to excellent ( α 0.82–0.94) for all PROMIS+HF‐27 scores and acceptable to good ( α /Spearman–Brown 0.60–0.85) for PROMIS+HF‐10 scores. Test–retest intraclass coefficients were acceptable to excellent (0.75–0.97). Both profiles demonstrated known‐groups validity for the overall and physical health summary scores based on NYHA class, and convergent validity for nearly all scores compared with KCCQ scores. In the longitudinal sample, we demonstrated responsiveness for PROMIS+HF‐27 and PROMIS+HF‐10 overall and physical summary scores. For the PROMIS+HF overall summary scores, a group‐based increase of 7.6–8.3 points represented a small to medium change (Cohen's d = 0.40–0.42). For the PROMIS+HF physical summary scores, a group‐based increase of 5.0–5.9 points represented a small to medium change (Cohen's d = 0.29–0.35). Conclusions: The PROMIS+HF‐27 and PROMIS+HF‐10 profiles demonstrated good psychometric characteristics with evidence of responsiveness for overall and physical health. These new measures can facilitate patient‐centred research and clinical care, such as improving care quality through symptom monitoring, facilitating shared decision‐making, evaluating quality of care, assessing new interventions, and monitoring during the initiation and titration of guideline‐directed medical therapy.